Bishte Broor - Mir, Rubayata Umeed (The Columbia Journal of Asia, 2024)
Bishte Broor is a story that explores the culture of Kashmir through animal-human relations. It throws light on different cultural aspects like folk music and traditions. It presents the cultural significance of wazwan at weddings. The tools used to make wazwan at weddings in Kashmir are also given a focus. The story illustrates how people in Kashmir treat stray animals and the belief that they should not be dependent on humans while living in their natural habitat. The story also uses the terms Bishte and Ded, derived from the names of two legends of Kashmir.